MASA KEEMASAN TEATER TRADISIONAL MENDU KALIMANTAN BARAT - Wirawan, Gunta; Waluyo, Herman J.; Suwandi, Sarwiji; Widodo, Sahid Teguh (Magistra Andalusia: Jurnal Ilmu Sastra, 2020)
The benefits of studying history, in addition to remembering the past, are also valuable lessons for future generations. Through history, the younger generation knows the cultural treasures of the nation so that they can preserve them. One of the original arts belonging to West Kalimantan is the traditional theater mendu. This theater was successful at the beginning of its emergence (1876 AD) until the Japanese colonial era. After that it was dim because society was forbidden by Japan to gather and associate. Mendu was bloated again and became the belle of the 80's which was driven by the maestro Sataruddin Ramli (1948 - 2015). However, this particular art of West Kalimantan is now only a memory. This research aims to describe the golden age of West Kalimantan's traditional theater. The method used is descriptive qualitative form with a literature study approach. The results of the study describe (1) the glory period from the beginning of the emergence of the mendu to the Japanese occupation (1876 - 1942), (2) the traditional theater of the mendu became the belle of the community (1980s - 2000s). Factors that cause the mendu golden period include because in the past the world of entertainment was not yet sophisticated and modern, the characteristics of the traditional and simple community, the story that was served favored by the community at that time, the participation of the Regional Government of West Kalimantan, as well as coaching was held for the younger generation.